Video Conference Application as a Media for EFL Students in Indonesia to Learn English: A Systematic Literature Review - I Kadek Teddy Jaya Nugraha; Made Hery Santosa; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology has increased the use of video conferencing applications in English as a Foreign Language (EFL) learning, particularly in online and blended learning environments in Indonesia. Applications such as Zoom, Google Meet, and OmeTV have been widely used to facilitate communication, interaction, and speaking practice among EFL students. Therefore, this study aimed to systematically review previous studies regarding the use of video conferencing applications as learning media for EFL students in Indonesia. Specifically, the study investigated the impact of Google Meet, OmeTV, and Zoom on students’ English learning outcomes, particularly speaking skills, pronunciation ability, and learning motivation. This study employed a Systematic Literature Review (SLR) method to identify, assess, and interpret relevant previous studies. Using the PRISMA framework, 15 studies were selected from an initial 198 studies for further analysis. The findings revealed that video conferencing applications positively contribute to improving students’ speaking skills, pronunciation ability, and learning motivation. Furthermore, video conferencing applications provide alternative learning media that can support teachers in creating more interactive and engaging English learning experiences.